Association of maternal serum concentrations of 2,2', 4,4'5,5'-hexachlorobiphenyl (CB-153) and 1,1-dichloro-2,2-bis (p-chlorophenyl)-ethylene (p,p'-DDE) levels with birth weight, gestational age and preterm births in Inuit and European populations - Wojtyniak Bogdan J; Rabczenko Daniel; Jönsson Bo AG; Zvezday Valentyna; Pedersen Henning S; Rylander Lars; Toft Gunnar; Ludwicki Jan K; Góralczyk Katarzyna; Lesovaya Anna; Hagmar Lars; Bonde Jens (BMC, 2010)
Abstract Background Epidemiological studies on the association between maternal exposure to persistent organic pollutants (POPs) and fetal growth alteration report inconsistent findings which weights in favor of additional studies. Methods Blood samples were collected from interviewed pregnant women in Greenland (572), Kharkiv (611) and Warsaw (258) and were analyzed for CB-153 and p,p'-DDE by gas chromatography-mass spectrometry. Data on birth weight, gestational age and preterm birth were obtained for 1322 singleton live births. We examined the association between natural log-transformed serum POPs concentration and birth weight and gestational age using multiple linear regression and the association with prematurity using logistic regression controlling for potential confounding factors. Results The median serum concentrations of CB-153 and p,p'-DDE were for Inuit mothers 105.6 and 298.9, for Kharkiv mothers 27.0 and 645.4 and for Warsaw mothers 10.7 and 365.2 ng/g lipids, respectively. Increase in CB-153 concentration by one unit on the log scale in Inuit mothers serum was associated with significant decrease in infant birth weight of -59 g and gestational age by -0.2 week. Decreases observed in the cohorts in Kharkiv (-10 g and -0.1 week) and in Warsaw (-49 g and -0.2 week) were not statistically significant. Increase in p,p'-DDE concentration by one unit on the log scale was associated with a statistically significant decrease in infant birth weight of -39.4 g and -104.3 g and shortening of gestational age of -0.2 week and -0.6 week in the Inuit and Warsaw cohorts, respectively. In the Kharkiv cohort decrease in birth weight (-30.5 g) was not significant, however a shortening of gestational age of -0.2 week per increase in p,p'-DDE concentration by one unit on the log scale was of the borderline significance. There was no significant association between CB-153 and p,p'-DDE concentrations and risk of preterm birth however, in all cohorts the odds ratio was above 1. Conclusions In utero exposure to POPs may reduce birth weight and gestational age of newborns however, new insights as to why results vary across studies were not apparent.